Less than equable Heronian triangles. Issue 549 (17th October 2016) - Dolan, Stan
Abstract : It is well known that there are precisely five integer-sided triangles which have equal area, Δ, and perimeter, P . These triangles are called equable Heronian triangles. A proof of this result was given by Whitworth [1]. Since Whitworth's time, much attention has been given to triangles whose areas are integer multiples of their perimeters, for example [2, 3]. However, as this paper will show, Heronian triangles with areas less than their perimeters have some mathematical interest.